ChemInform Abstract: Tungstate Based Poly(ionic Liquid) Entrapped Magnetic Nanoparticles: A Robust Oxidation Catalyst. Issue 7 (18th February 2014) - Pourjavadi, Ali; Hosseini, Seyed Hassan; Moghaddam, Firouz Matloubi; Foroushani, Behzad Koushki; Bennett, Craig
Abstract The recoverable catalyst can be separated from the reaction mixture using an external magnet and reused at least ten times without loss of its catalytic activity.